THE EFFECT OF WORK-LIFE FLEXIBILITY POLICY ON PERFORMANCE AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB): WITH BURNOUT AS A MEDIATOR VARIABLE - Sefiana Putri Suleman; Ade Solahudin; Eteh Resa Asyifa (CV. Radja Publika, 2026)
This study aims to analyze the effect of Work-Life Flexibility Policy on employee performance and Organizational Citizenship Behavior (OCB), with burnout as a mediating variable. The study used a quantitative approach with an explanatory research method. Data were collected through questionnaires from employees of PT Kaiti Global Indonesia and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the help of SmartPLS. The results of the study indicate that Work-Life Flexibility Policy has a negative and significant effect on burnout and a positive and significant effect on employee performance and OCB. Burnout has a negative and significant effect on performance and OCB, and is proven to mediate the relationship between Work-Life Flexibility Policy and employee performance and OCB. This study concludes that the implementation of an effective work flexibility policy can reduce burnout, thereby improving performance and encouraging employee OCB behavior.